Performance of FDSOI double-gate dual-doped reconfigurable FETs. (August 2022) - Navarro, C.; Donetti, L.; Padilla, J.L; Medina, C.; Ávila, J.; Galdón, J.C.; Recio, M.; Márquez, C.; Sampedro, C.; Gámiz, F.
Highlights: Dual doped Reconfigurable FETs are functional with two top gates. Dual doped RFETs have greater currents than Schottky barrier RFETs. DD RFETs are more immune to manufacturing variability than SB RFETs. DD RFETs are appealing for 28 FDSOI technology to implement in-situ reprogrammable logic. Abstract: In this work, the electrical performance of a novel reprogrammable FDSOI device with dual-doping at source/drain and only two top gates is investigated through advanced 3D TCAD simulations. The static and dynamic operations are evaluated and compared with those of traditional Schottky barrier RFETs and standard 28 nm FDSOI MOS transistors under manufacturable geometries.